Implementing Swakelola III Framework of Open Data 1.0 at Diskominfo Bengkayang Regency and IT Department of Shanti Bhuana Institute - Azriel Christian Nurcahyo; Fitria Elvi; Rifqi Hammad (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The implementation of information systems and technology within the scope of Governmentis now mandatory to adhere to a framework known as Swakelola. The framework necessitates that every system and technology project involving local community organizations or regencies should develop the existing human resources potential within the city. This also applies to the procurement of open data systems managed by the Department of Communications and Informatics of Bengkayang Regency, involving the IT Department of Shanti Bhuana Institute through direct appointment based on Type III (Swakelola). The creation of the Open Data system is named Open Data 1.0, aiming at facilitating the Regent in accessing data from the Regional Work Units in Bengkayang Regency for easier future monitoring. The Swakelola implementation involves various documents that are expected to assist other universities in establishing official collaborations with the Local Government for system development. The feedback from the collaboration on creating Open Data 1.0 obtained a satisfaction rating of 4.6 out of 5 from the Head of the IT Division and the Users of Diskominfo Bengkayang Regency.